Trends in prevalence of esophageal adenocarcinoma: Findings from a statewide database of over 6 million patients - Qumseya, Bashar; Yang, Shuang; Guo, Yi (Endoscopy International Open, 2024)
Esophageal cancer (EC) is a leading cause of cancer-related death in the west 1. Esophageal squamous cell carcinoma (SCC) is the most common type of EC worldwide. However, in Western countries, including the United States, esophageal adenocarcinoma (EAC) is the most common 2. EAC is most common in the lower esophagus whereas SCC is most common in the middle and upper esophagus 3. The incidence of EAC has increased dramatically in western countries over the past few decades. 23 The exact reason for this rise in EAC has not been clearly understood. However, an increase in the prevalence of EAC risk factors is postulated as a potential explanation 4. Although there are many identifiable EAC risk factors, including gastroesophageal reflux disease (GERD), obesity, male sex, White race, and smoking 567, Barrett’s esophagus (BE) remains the major precursor lesion of esophageal adenocarcinoma. BE develops when there is a change in the normal squamous lining of the esophageal mucosa into intestinal metaplasia 89. The incidence has also increased in the population over the past few decades 1011. There is a well-described progression within BE from non-dysplastic BE (NDBE), low-grade dysplasia (LGD), high-grade dysplasia (HGD), intramucosal carcinoma (IMC), to invasive EAC 1213. Recent data suggest that the increased incidence of EAC may have plateaued 1. However, we questioned whether the prevalence of EAC is still increasing, especially at younger ages in lieu of recent trends showing an increase in the prevalence of colorectal cancer in younger patients. These findings resulted in a lowering of the colorectal cancer screening age cutoff to 45 years from 50 years 141516. Therefore, we aimed to assess the time trends in the prevalence and incidence of EAC and some of its risk factors in a large population of patients in Florida and to assess these trends based on age categories. We hypothesized that the prevalence of EAC and BE has increased over time at younger age groups.
Keywords: Reflux disease; Barrett's and adenocarcinoma; Epidemiology